Fatigue Crack Propagation in AlSi10Mg Additive Manufactured Aeronautical Parts Processed by Laser Shock Peening - Chinyama, Joel (University of the Witwatersrand, Johannesburg, 2024)
Additive manufacturing (AM) offers advantages for complex aeronautical parts, but inherent defects can reduce fatigue life. Post-processing techniques such as laser shock peening (LSP) can be used to introduce beneficial compressive residual stress that hinders crack propagation. This study investigates LSP as a method to improve fatigue performance in additively manufactured AlSi10Mg aeronautical parts. It examined how varying LSP treatment laser power intensity (1.5 – 4.5 GW/cm2) affects LSP's effectiveness and identified optimal LSP residual stress profiles for peak fatigue performance. The residual stress profiles that were used in this research were adopted from previous experimental work done on AM-manufactured AlSi10Mg alloys within the Wits AM/LSP group. Previous experimental work results on wrought AA2024-T351 (untreated and LSP-treated cases) indicated that LSP-treated samples have a fatigue life of at least four times longer as compared to as-built samples. AFGROW models with similar geometry, material properties and load conditions were used to predict the fatigue life of as-built and LSP-treated cases. An improvement in fatigue life of at least 3.8 times was observed, which was within an acceptable deviation from the experimental results. These results were used to validate AFGROW models for exploring different specimens. Fracture mechanics models (AFGROW) were used to compare the fatigue life of as-built and LSP-treated AlSi10Mg samples with different LSP power intensity parameters. The results showed that LSP treatment can significantly extend fatigue life, with the optimal laser power intensity found to be 3.0 GW/cm2. This improvement is attributed to the introduction of compressive residual stresses by LSP, which suppress crack initiation and propagation. The effectiveness of LSP was further explored in the context of the Cessna 172/175 horizontal stabilizer, a part that could benefit from AM for weight reduction and structural integrity. AFGROW models were developed to predict the fatigue life of the centre lightening hole in the forward spar, a critical location for crack initiation. The models incorporated a beta correction factor to account for the specific crack geometry and stress distribution. The beta correction factor was determined by comparing the stress intensity factors from the Finite Element Analysis (FEA) and AFGROW models. The results again demonstrated a significant increase in fatigue life (of at least six times) for LSP-treated parts compared to as-built parts. AFGROW models with a beta correction factor proved valuable for predicting fatigue life in components with complex geometries. This study confirms that LSP is an effective post-processing technique for mitigating fatigue crack propagation in AlSi10Mg AM aeronautical parts.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Additive Manufacturing; Laser Shock Peening; Crack Propagation; Fatigue; AlSi10Mg; SDG-9: Industry, innovation and infrastructure